الكفايات التدريسية لأستاذ التربية البدنية والرياضية وعلاقتها باتجاهات الإناث نحو ممارسة النشاط البدني الرياضي التربوي في مرحلة التعليم المتوسط - قدال، زين الدين; بلقاسم، دودو Doudou, Belqassem (جامعة العربي بن مهيدي أم البواقي - معهد علوم وتقنيات الشاطات البدنية والرياضية, 2017)
هدفت الدراسة إلى معرفة العلاقة بين الكفايات التدريسية واتجاهات الإناث نحو ممارسة النشاط البدني الرياضي التربوي في مرحلة التعليم المتوسط، استخدمنا المنهج الوصفي، وتم اختيار عينة بالطريقة العشوائية من مجتمع البحث والتي شملت على (150) تلميذة و (15) أستاذا بمرحلة التعليم المتوسط بمقاطعة بني حواء – ولاية الشلف، وكأداة لجمع البيانات فقد اعتمد الباحثان على مقياس الكفايات التدريسية لأساتذة التربية البدنية والرياضية، من إعداد كل من "أحمد زكي صالح" و "رمزية غريب" حيث يحتوي على (44) عبارة مقسمة إلى أربع محاور: تخطيط البرامج، التواصل، التقويم، طرق وأساليب التدريس، كما تم تطبيق مقياس الاتجاهات نحو النشاط البدني الرياضي، والذي صمم من طرف كينيون وترجمه إلى العربية (محمد حسن علاوي)، يتكون من (06) أبعاد و (54) عبا ة شاملة على النشاط البدني كخبرة، النشاط البدني للياقة والصحة، النشاط البدني لخفض التوتر، النشاط البدني كخبرة للتفوق الرياضي، وكوسائل للمعالجة الإحصائية وتحليل النتاج استخدمنا برنامج الحزمة الإحصائية للعلوم الاجتماعية SPSS، وأثبتت نتائج الدراسة بأنه توجد فروق في الكفايات التدريسية لدي الأساتذة تعزي إلي متغير الخبرة المهنية، كما أثبتت انه لا توجد فروق في اتجاهات الإناث نحو ممارسة النشاط البدني الرياضي التربوي تعزي إلي متغير الكفاية التدريسية لأستاذ التربية البدنية والرياضية.
The aim of the study is to find out the relationship between the Teaching competencies and attitudes of females toward the educational physical and sporting activity in the phase of middle school ,To Achieve this aim the researchers used the descriptive method considering that the nature of the subject imposes The method in the research , the specimen was selected randmoly , which included (150) students and (15) teachers at the middle school in the province of Beni Hawa – chlef state , in order to collect the information , the researchers relied on the measure of teaching competencies to be applied on the teachers of physical education and sports, this measure was prepared by Mr :"Ahmed Zaki Saleh" and Ms : "Ramziya Gharib " . The measure contains (44) terms divided into four ‘04’ dimensions : Program Planning , Communication , evaluation , methods of teaching , in addition to this we used a measure of attitudes toward the sporting and physical activity , this was designed by Mr:( kinion ) and translated to Arabic Mr :(Mohamed Hassan Allawi) , the measure contains ( 06) dimensions and ( 54 ) terms including : Physical activity as an experience, physical activity for fitness and health, physical activity to reduce stress, physical activity as an experience of sporting superiority , As regards to statistical analysis , the researchers used the SPSS program , the results of the study proved that There are no statistically significant differences in the attitudes of females towards the practice of sport physical education attributed to the variable Teaching competencies of the teachers of physical education and sports.
Keywords: الكفايات التربوية -- الأنشطة الرياضية -- معلمو التربية البدنية -- ممارسة الرياضة -- الرياضة النسائية